An object finder for the visually impaired - Lee, Boon Cheng. (2010)
Technology is changing rapidly nowadays and is bringing radical changes and opportunities to our society. Computer and image capturing device such as web camera are becoming more common in our daily life. However, there are still some of the population who are not able to fully utilize the technology such as the disadvantage people who are visually impaired. In fact, technology does able to help these disadvantages people in coping with the difficulties that they are facing every day.